Case report: tongue squamous cell carcinoma after renal transplantation - Nascimento, Suellen Vieira do; Macedo, Adriana Furtado de; Souza, Cynthia Larissa Cordeiro de; Pestana, José Osmar Medina; Kalinin, Yuri (Journal of Oral Diagnosis, 2018)
The continuous immunosuppression of patients undergoing solid organ transplantation leaves them susceptible to the development of a wide variety of neoplasias, increasing their risk in relation to the general population. The present article presents a case report of squamous cell carcinoma in the tongue of a 57 year-old man fifteen years after a live donor kidney transplant. In use of several medications, he presented several comorbidities in the post-transplant period. One of these, Kaposi’s sarcoma, is quite common in organ transplanted individuals associated with HHV-8. In this specific case, the neoplasia had the oral cavity as the primary site and the Oral Medicine team had an important role in the diagnosis of the lesion and treatment of its comorbidities, and this care was the motivation of this article.